PELATIHAN OPTIMALISASI MEDIA SOSIAL UNTUK MENAMBAH CUAN PADA WARGA BELAJAR PKBM - Yunita Indriany; Nika Sintesa; Darmawan Darmawan; Setiawan Setiawan; May Vitha Rahmadhani (JURNAL ABDIMAS PLJ, 2022)
Currently, the advancement of digital technology, including social media (medsos) in it, can now be maximized for all needs. Not only to communicate but also to maintain existence, to run a business. The prolonged pandemic that has made almost all activities carried out using technology has triggered the massive optimization of social media to occur. Social Media is increasingly becoming an option that is often used by brands to expand their products. From the need to use Social Media as a place to peddle products and services, in the end emerged the profession of influencers, content creators, key opinion leaders (KOL) who competed in terms of creativity in presenting content. The community and the younger generation are expected to be able to take advantage of social media and the internet as best they can in order to increase their income through social media. not just for playing games and watching videos for hours. In order to improve the knowledge, skills and mental attitudes needed to develop themselves and work for a living, prepare provisions to face the world of work. This community service activity was carried out for PKBM Negeri 23 Learning Citizens, Kebon Melati, especially Learning residents who had difficulties in the midst of the Covid-19 pandemic. This activity is carried out online. To help the Learning Citizens, several series of activities were carried out, namely training and the application of Social media in buying and selling transactions, as well as workshops on new businesses that are suitable to be run in the New Normal era The output of this activity is that the Training Participants can use Social Media in buying and selling activities. From the results of the evaluation and findings, it can be concluded that the community service program provides additional insight into knowledge about the concept of Social Media in the Digital Era so as to increase income for Training ParticipantsKeywords: Cuan, Digital, Social Media